2007
DOI: 10.1002/eji.200737184
|View full text |Cite
|
Sign up to set email alerts
|

On watching the watchers: IDO and type I/II IFN

Abstract: A series of recent studies, including an article in this issue of the European Journal of Immunology, have demonstrated that the immunoregulatory pathway of tryptophan catabolism, initiated by the enzyme indoleamine 2,3-dioxygenase (IDO), not only represents an effector mechanism of peripheral tolerance, but is also a critical participant in the promotion of an optimally protective immune response balanced between inflammation and tolerance. Although subjected to transcriptional regulation by type I/II IFN, ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 22 publications
1
65
0
5
Order By: Relevance
“…In five independent experiments, knockdown of TLR-7 induced 60% ± 16% less IDO expression (P < 0.05, Student t test). Low levels of IFN-γ did not induce IDO expression under these conditions, as reported previously (25). These data indicate that TLR-7-mediated activation of the noncanonical NF-κB pathway is important for IDO expression in human pDCs.…”
Section: Resultssupporting
confidence: 87%
“…In five independent experiments, knockdown of TLR-7 induced 60% ± 16% less IDO expression (P < 0.05, Student t test). Low levels of IFN-γ did not induce IDO expression under these conditions, as reported previously (25). These data indicate that TLR-7-mediated activation of the noncanonical NF-κB pathway is important for IDO expression in human pDCs.…”
Section: Resultssupporting
confidence: 87%
“…The most potent mechanism to limit growth of intracellular chlamydiae in human cells is tryptophan depletion upon IFN-γ-induced up-regulation of IDO. Direct immune regulatory functions of IDO and the tryptophan catabolite kynurenine on intracellular chlamydiae are still discussed controversially (17,18). We observed that in hypoxia IDO mRNA and protein expression ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Sustained IDO induction depends on noncanonical NF-kB activation (19). Because TRIF-mediated signaling may involve noncanonical NF-kB family members (38,39), we hypothesized that a TLR7/TRIF axis could be at work in IDO induction by GpC-ODN.…”
Section: Discussionmentioning
confidence: 99%
“…In most experimental settings of chronic inflammation and autoimmunity, the protective effects of TLR9 ligation are associated with the induction of IDO, an enzyme thatinitiating the suppressive mechanisms of tryptophan depletion and kynurenine production (18)-is operative in both the innate and adaptive forms of immunity (13,19).…”
mentioning
confidence: 99%